Peritonitis due to Moraxella osloensis: A case report and literature review. Issue 12 (December 2019) - Yamada, Ayano; Kasahara, Kei; Ogawa, Yoshihiko; Samejima, Kenichi; Eriguchi, Masahiro; Yano, Hisakazu; Mikasa, Keiichi; Tsuruya, Kazuhiko
Abstract: A-26-year-old man was admitted to our hospital with diffuse abdominal pain, nausea, and vomiting. He had a history of malignant nephrosclerosis, for which he had been receiving peritoneal dialysis (PD) for the past 14 months. His PD effluent was cloudy and turbid (white blood cell count, 10, 528/μL; neutrophils 95.2%). A Gram-negative coccobacillus was isolated from peritoneal fluid culture. However, the organism could not be identified by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) (Vitek MS, bioMérieux), but was identified as Moraxella osloensis by the 16S rRNA gene sequencing. He was successfully treated with intraperitoneal cefazolin therapy for 3 weeks without removing the intra-abdominal catheter. A literature review revealed three previous case reports all of which were diagnosed by MALDI Biotyper (Bruker Daltonics), suggesting that the identification of M. osloensis may vary depending on the type of MALDI-TOF MS system. In conclusion, we experienced a case of M. osloensis infection in a PD patient, which was successfully treated by antibiotic treatment, without removing the PD catheter.